Desempenho de escolares com dislexia: programas de intervenção metalinguistico e de leitura - Germano, Giseli Donadon [UNESP] (2013)
Dyslexia is specific learning disabilities, of neurological origin, resulted from a phonological deficit of language. This study aims to verify the performance of students with dyslexia in phonological intervention program, reading program, and phonological and reading remediation program in students with dyslexia. The participants of this study were 60 students who were divided as follows: GI (ten students with dyslexia submitted to phonological remediation program and ten students with dyslexia not submitted to phonological remediation program), GII (ten students with dyslexia submitted to reading program and ten students with dyslexia not submitted to reading program), GIII (ten students with dyslexia submitted to phonological and reading program and ten students with dyslexia not submitted to phonological and reading program). The phonological and reading remediation was applied in three phases: pretest, training, post-testing. The results showed significant statistical difference between two evaluation moments, revealed better performance in the cognitive-linguistic skills in post-test situation comparing to the pretest, showing the efficacy of the three remediation programs for students with dyslexia. The better performance of the students with dyslexia submitted to the remediation programs shows the necessity of phonological instruction or phonological instruction with reading to be offered in the literacy context, once this will help students to develop cognitive-linguistic skills to learn the alphabetic basis of the Brazilian Portuguese writing system.